Atypical Presentation of Cat‐Scratch Disease in a 30‐Year‐Old Female: A Case Study - Elham Mohammed Khatrawi; Neo Zhong Yi Benjamin; Pugazhendi Inban; Sai Sakthi; Omniat Amir Hussin (Clinical Case Reports)
ABSTRACT Cat‐scratch disease (CSD) is a zoonotic infection caused by the Gram‐negative bacterium Bartonella henselae, typically transmitted through the scratch or bite of a cat. This case report highlights an atypical presentation of CSD in a 30‐year‐old female pet groomer with prolonged fever, fatigue, and axillary lymphadenopathy. The patient's diagnosis was confirmed through histopathological findings of necrotizing granulomas and subsequent improvement after targeted antibiotic therapy with azithromycin. The case emphasizes the diagnostic challenges posed by atypical presentations of CSD, especially in regions with high cat exposure. This case also underscores the importance of considering CSD in the differential diagnosis of febrile lymphadenopathy and highlights the efficacy of antibiotic therapy in symptom resolution.